전세사기의 발생원인과 대응방안에 관한 연구 - 강민채(Minchae Kang); 안정빈(Jeongbin Ahn) (한국콘텐츠학회 논문지, 24(9), 2024)
최근 주택가격의 급등락으로 인한 전세사기가 사회적으로 문제화가 되고 있다. 전세사기 문제가 발생한 초창기에는 수도권 일부 지역에 국한된 문제로 인식되었지만, 이제는 사회 문제로까지 인식되고 있다. 전세사기의 피해자들은 대부분 사회적 약자로 분류될 수 있는 신혼부부나 사회초년생 등 20대, 30대 젊은 층에 집중되어 있는 경향이 있다. 전세가격의 급등에는 과대 평가된 담보가치 인정제도를 비롯해 금융기관 전세보증 대출에 대한 관대한 관행도 한 요인으로 지적될 수 있을 것이다. 그러나 최근 고금리 추세로 인한 부동산 가격의 급락세의 영향으로 소위 역전세로 인한 전세사기 문제가 발생하고 있다. 이러한 전세사기 사태를 계기로 전세보증금반환금액 확대, 전세보증금 관리시스템 재구축, 임차권 공시방법 보완 등을 통하여 임차인 보호 방안을 다시 한번 재검토해야 할 필요성이 있다. 또한 형법적 관점에서의 처벌가능성에 대해서도 고찰해 보아야 한다. The problem of housing rental fraud has spread nationwide and is emerging as a social problem. Most of the victims are concentrated in young people in their 20s and 30s, such as newlyweds and beginners in society. There have been similar cases in the past, but recently, as housing prices fell due to rising bank interest, it began to emerge as a criminal law problem, and measures were needed. In other words, it is necessary to consider ways to protect tenants, such as expanding the amount of rental deposit returns, maintaining the rental deposit management system, and informing housing rent in various ways. In addition, the possibility of punishment from a criminal law perspective should be considered. KCI Citation Count: 0